The Impact of Bureaucratic Structures on the Performance of School Principals in Public Secondary Schools - Nwafor, Innocent Nnochiri; Ololube, Prince Nwachukwu (Three E Science Institute, 2024)
The study investigated into bureaucratic role of principals’ leadership performance in public senior secondary schools in Rivers State. The study adopted the descriptive research design. The population of the study consisted of the two hundred and ninety six (296) principals in all the two hundred and ninety-six (296) public senior secondary schools in the 23 Local Government Areas of Rivers State. The sample of this study comprised the two hundred and ninety-six (296) principals selected from the two hundred and ninety-six (296) public senior secondary schools in the twenty three (23) Local Government Areas in Rivers State, representing 100% of the population using the census sampling technique. Out of the 296 copies of questionnaires distributed 275 representing 96% of the total number of copies, were duly completed and returned. The instrument for data collection for this study was a 30 item self-structured questionnaire titled ‘Bureaucratic Role of Principals’ Leadership Performance Questionnaire (BRPLPQ)”. The instrument was structured using the modified 4-points Likert Scale model of; Very High Extent (VHE) – 4 points; High Extent (HE) =3 points; Low Extent (LE) = 2 point and Very Low Extent (VLE) =1 point.